Pengembangan Potensi Dana Zakat Produktif Melalui Lembaga Amil Zakat Untuk Meningkatkan Kesejahteraan Masyarakat - Ainun Nashih Syahbana (Jurnal Ekonomi Islam, 2026)
This study aims to analyze the development of the potential for productive zakat funds through the strategic role of Zakat Management Institutions (LAZ) in improving community welfare. The method used is a qualitative approach in the form of a literature review (library research), analyzing various academic texts, previous studies, and regulations related to zakat management. The main findings indicate that LAZ plays a crucial role not merely as a charity distributor, but as a business incubator agent for mustahik through sharia-based business financing programs and continuous mentoring (actuating). The utilization of this productive zakat holistically contributes to improving the welfare of mustahik, both materially (economic independence) and spiritually. The implication of this study encourages LAZ and policymakers to prioritize fund allocation for economic empowerment programs and improve amil’s capacity in business mentoring to accelerate the social mobility of mustahik transforming into muzakki.